Assessment of Sexual Dimorphism in Mental Foramen Position Using Panoramic Radiographs: A Retrospective Study in Adult Patients: Implications for Clinical Practice and Forensic Identification - Aulia Rahmaniyah Siregar; Kemala Hayati; Rachmi Fanani Hakim; Ridha Andayani; Afrina Afrina; Abdillah Imron Nasution (Journal of Syiah Kuala Dentistry Society, 2025)
The mental foramen is an important anatomical structure of the mandible that exhibits positional variations influenced by age, sex, and ethnicity. Its location is clinically relevant in various dental and surgical procedures, including implant placement and local anesthesia administration. Previous studies have reported inconsistent findings regarding sexual dimorphism in the position of the mental foramen. This study aimed to evaluate differences in the vertical and horizontal positions of the mental foramen between adult males and females using panoramic radiographs. This analytical observational study employed a cross-sectional design involving 60 panoramic radiographs (30 males and 30 females) obtained from retrospective patient records at the Dental and Oral Hospital of Universitas Syiah Kuala (RSGM USK), Banda Aceh, in 2023. Measurements of the mental foramen position were performed using Cliniview 11.5 software. Data analysis was conducted using the Independent Sample t-test for vertical position measurements and the Mann–Whitney U test for horizontal position analysis. The results demonstrated a significant difference in the vertical position of the mental foramen between males and females (p < 0.05), with males exhibiting greater vertical distances. No significant difference was observed in the horizontal position (p > 0.05), although descriptively the mental foramen in males tended to be located more posteriorly compared to females. In conclusion, sexual dimorphism was identified in the vertical position of the mental foramen but not in its horizontal position. These findings are clinically important for dental treatment planning to minimize iatrogenic complications and improve procedural accuracy.